A consulta de puericultura na perspectiva de mães e profissionais de Unidades Básicas de Saúde de Belo Horizonte. - Poliana Reginele de Melo Dias (2017)
Systematic monitoring of child growth and development is a fundamental practice in Primary Health Care, with a direct impact on morbidity and mortality rates. Childcare promotes children's quality of life, avoiding early deaths and hospitalizations, and allowing the child to develop his full potential. Considering that the average number of childcare services is lower than expected in the city of Belo Horizonte, this study sought to understand the perspectives of mothers and professionals about this consultation, in order to reveal objective and subjective aspects that may be related to the low averages. This is a qualitative research, grounded in the theory of social representations. The study scenario included basic units with high and low childcare averages. The data collect was conducted through focus groups with professionals who make the childcare, and interviews with mothers of children under two years old, frequent or not to consultations. Data analysis was performed according to the structural analysis of narration method. 28 professionals participated: 13 nurses, 11 family physicians and four pediatricians; the interviews were made with 14 mothers. The professionals recognized the childcare as an instrument of prevention of diseases and health promotion. The results demonstrate that the action of the 5th day facilitates childcare in the units in which this work process is well organized, coinciding with a higher average of attendance. The professionals of units with lower average said that they dont feel qualified in the child care, a problem aggravated by the low number of pediatricians in the basic units. They also affirmed that the mothers' frequency to the consultation is low, relating it to the low knowledge of the importance of childcare, indifference and difficulties to getting out of work. However, in the interviews with the mothers, the work was not cited as an obstacle to the consultations, but the distance from the unit, little financial resources and inattention with the date. The majority of mothers did not recognize the term childcare or understand superficially the importance of this monitoring. They say that they come to the unit mainly when the child is sick. Mothers consider the consultation is satisfactory when the provider attends the child integrality, but reports that, if changes are found, referral to specialists may be difficult. Some mothers observe differences between the consultations of nurses, generalists or pediatricians, and the results indicate that the permanence of the biomedical model in representations about health care as a central impediment to the organization of services and adherence to the activities of promotion and prevention in childcare. It is expected that this research contributes to discussions in the health units, enabling strategies that favor childcare, contributing to the improvement of the infants' uptake, the frequency of mothers to consultations and the quality of actions. To this end, it is suggested that the professionals be trained and that pediatricians be included to complete the support teams to offer qualified primary care so that the child can grow up in a healthy way.